Mobility plan for the General Hospital Novo mesto: steps towards reducing environmental impacts and increasing climate resilience - Urh, Vane (Journal for Geography, 2024)
The article presents the process of creating a mobility plan for General Hospital Novo mesto and its contribution to reducing the environmental impact of both the healthcare and traffic sectors. It specifically presents an analysis of travel habits and measures that contributed to promoting and raising awareness of sustainable mobility in a high-traffic area. Additionally, by an importance-performance analysis, we tried to determine the factors that could most influence the change in travel habits in the direction of more sustainable mobility. A shift in modal split towards more sustainable mobility will contribute to the green transition and impact both adaptation to and mitigation of climate change.